Integrating MDGs into the Malawi Social Action Fund - Lenneiye, N. Mungai (World Bank, Washington, DC, 2012)
Responding to endemic poverty in Malawi, the government has consulted with communities, civil society, the private sector and other stakeholders in formulating a Malawi Poverty Reduction Strategy Paper (MPRSP). The MPRSP is based on four 'pillars' -- promoting economic growth, enhancing human development, protecting the vulnerable, and promoting good governance. Within these, the broad issues of HIV/AIDS, gender inequalities, environmental degradation, and slow technological innovation in society are addressed.